2017
DOI: 10.3390/min7040063
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Strata Behavior during Thick Seam Mining by Fully-Mechanized Top Coal Caving in a Loess-Covered Gullied Region

Abstract: This study systematically investigates the overburden movement and strata behavior at a fully-mechanized top coal caving (FMTCC) face in a thick coal seam in a loess-covered gullied region by field measurement and theoretical analysis. A comparative analysis was performed to examine how the attitude of surface gullies and the structure of overburden affect face support resistance. The characteristics and evolution mechanism of strata behavior during FMTCC under gully slopes in a loess-covered gullied region we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Mining activity at a single longwall face in the UCS will cause destruction of the old roof stratum following a vertical "O-X" pattern, after which a "masonry beam" structure will form in the overlying stratum. [26][27][28][29][30][31] As demonstrated by a considerable number of studies, [31][32][33][34][35][36][37] the mining activities at multiple longwall faces will enlarge the fracture zone of the overlying stratum when the coal seam is deeply buried. In this case, the key layers located in the upper middle part of the fracture zone far away from the coal seam may experience rotation or fracturing and become unstable.…”
Section: Ucs Main Roofmentioning
confidence: 99%
“…Mining activity at a single longwall face in the UCS will cause destruction of the old roof stratum following a vertical "O-X" pattern, after which a "masonry beam" structure will form in the overlying stratum. [26][27][28][29][30][31] As demonstrated by a considerable number of studies, [31][32][33][34][35][36][37] the mining activities at multiple longwall faces will enlarge the fracture zone of the overlying stratum when the coal seam is deeply buried. In this case, the key layers located in the upper middle part of the fracture zone far away from the coal seam may experience rotation or fracturing and become unstable.…”
Section: Ucs Main Roofmentioning
confidence: 99%
“…Due to the movement of the 4th siltstone of SKS 1 being that of a voussoir, and h 2 = 24 m. By substituting the aforementioned parameters of the working face into inequality (31), it is clear that inequality (31) is not satisfied. Therefore, it can be deduced that the breaking of SKS 2 does not influence SKS 1; the support working resistance of LW30101 should thus be calculated according to formula (34).…”
Section: Lw30101 Hanglaiwan Coal Minementioning
confidence: 99%
“…Many studies were performed on the aforementioned issues related to FMFLMH, and their results have indicated that the key to solving the aforementioned issues is to determine the support working resistance of the working face. [26][27][28][29][30][31] For example, Gong and Jin 26 established two calculation models of support working resistance under a voussoir beam structure and the cantilever structure of SKS 1 to determine working resistance in FMFLMH. In the empirical formula method, empirical estimation formulae (Table 1), are used to calculate the support working resistance of the longwall faces with normal mining height 20 ; however, with the increase in extraction height, especially FMFLMH, determination of the support working resistance by empirical estimation cannot guarantee safe mining of the face.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In China, fully mechanized top-coal caving mining in ultra-thick coal seams (especially in 14-20 m ultra-thick coal seams) has developed rapidly in the past 10 years [1][2][3][4]. Studies in topics such as equipment matching, wall stability, strata control technology, safety guarantee technology for low gas occurrence and high gas emission have made important progress [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%